Combining Induced Pluripotent Stem Cells and Genome Editing Technologies for Clinical Applications. Issue 3 (March 2018) - Chang, Chia-Yu; Ting, Hsiao-Chien; Su, Hong-Lin; Jeng, Jing-Ren
In this review, we introduce current developments in induced pluripotent stem cells (iPSCs), site-specific nuclease (SSN)-mediated genome editing tools, and the combined application of these two novel technologies in biomedical research and therapeutic trials. The sustainable pluripotent property of iPSCs in vitro not only provides unlimited cell sources for basic research but also benefits precision medicines for human diseases. In addition, rapidly evolving SSN tools efficiently tailor genetic manipulations for exploring gene functions and can be utilized to correct genetic defects of congenital diseases in the near future. Combining iPSC and SSN technologies will create new reliable human disease models with isogenic backgrounds in vitro and provide new solutions for cell replacement and precise therapies.